2010
DOI: 10.1186/1471-2415-10-13
|View full text |Cite
|
Sign up to set email alerts
|

Macular thickness measurements in healthy Norwegian volunteers: an optical coherence tomography study

Abstract: BackgroundEthnic, intersubject, interoperator and intermachine differences in measured macular thickness seem to exist. Our purpose was to collect normative macular thickness data in Norwegians and to evaluate the association between macular thickness and age, gender, parity, and contraception status.MethodsRetinal thickness was measured by Stratus Optical Coherence Tomography in healthy subjects. Mean macular thickness (MMT) was analyzed by repeated measures ANOVA with three dependent regional MMT-variables f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 63 publications
(82 reference statements)
6
14
1
Order By: Relevance
“…This finding is supported by those of previous studies that found that males have thicker foveal measurements than female counterparts 20,24,25. As the difference in retinal thickness between genders seems to be greater in younger populations (as opposed to older adults), it has been suggested that a gonadal hormonal influence may contribute to this finding 24…”
Section: Discussionsupporting
confidence: 86%
“…This finding is supported by those of previous studies that found that males have thicker foveal measurements than female counterparts 20,24,25. As the difference in retinal thickness between genders seems to be greater in younger populations (as opposed to older adults), it has been suggested that a gonadal hormonal influence may contribute to this finding 24…”
Section: Discussionsupporting
confidence: 86%
“… 5 Also, thickness changes of all retinal layers can be measured in a 1, 3, and 6 mm diameter grid, although there is a high concordance in measured mean macular thickness in the central areas by the shorter (3.45 mm) and the longer (6 mm) scan length mapping protocols. 21 A further limitation in our study was using neither a longitudinal nor epidemiological design.…”
Section: Discussionmentioning
confidence: 98%
“…The partial correlation test was used to determine the effect of age on individual layer thickness with spherical equivalent (SE), 8 , 2 2 Topcon ima ge QF, 8 , 2 3 , 2 4 and sex 2,4,5,9,15,[25][26][27][28][29] as confounders, since these parameters are known to influence OCT thickness measurements. Bonferroni corrections were applied to counteract the effect of multiple testing with statistical significance set at P < 0.001.…”
Section: Discussionmentioning
confidence: 99%